Conflict resolution and religious behavior: Achieving authentic happiness among married individual - Dea Intan Purwanti; Annisa Fitriani; Rahmad Purnama (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2026)
This study aims to examine the relationship between conflict resolution, religious behavior, and authentic happiness among married couples in Lampung Province. This research employed a quantitative approach. The sample consisted of 100 married individuals residing in Lampung Province, selected through purposive sampling based on the following criteria: having been married for at least five years, having experienced marital conflict, not currently undergoing divorce or legal proceedings, and regularly engaging in religious practices. Data were collected through self-report questionnaires using a Likert scale. The data were analyzed using multiple linear regression analysis. The results indicated that the independent variables jointly had a significant effect on authentic happiness (F = 82.797, p < 0.05). Conflict resolution and religious behavior together explained 62.3% of the variance in authentic happiness, while the remaining 37.7% was accounted for by other variables not examined in this study.